Long non-coding PRNCR1 regulates the proliferation and apoptosis of synoviocytes in osteoarthritis by sponging miR-377-3p - Guan Wang; Chunhong Li; Xihai Zhang; Lian Tang; Yao Li (Journal of Orthopaedic Surgery and Research, 2022)
Abstract Background LncRNA PRNCR1 has been reported to be involved in LPS-induced inflammation, which contributes to osteoarthritis (OA). We predicted that miR-377-3p could bind to PRNCR1.MiR-377-3p can suppress OA development. We therefore analyzed the potential interaction between them in OA. Methods Expression of miR-377-3p and PRNCR1 in both OA (n = 40) and control (n = 40) samples were analyzed by RT-qPCR. MiR-377-3p or PRNCR1 were overexpressed in synoviocytes to explore their potential interaction. The subcellular location of PRNCR1 was analyzed by nuclear fractionation assay. The direct interaction between miR-377-3p and PRNCR1 was analyzed by RNA-pull down assay. The proliferation and apoptosis of synoviocytes were analyzed by BrdU and apoptosis assay, respectively. Results PRNCR1 was overexpressed in OA, while miR-377-3p was downexpressed in OA. PRNCR1 was detected in the cytoplasm and directly interacted with miR-377-3p. Interestingly, overexpression of PRNCR1 and miR-377-3p showed no regulatory role in each other’s expression. LPS treatment increased PRNCR1 expression and decreased miR-377-3p expression. PRNCR1 overexpression decreased LPS-induced synoviocyte proliferation and increased LPS-induced synoviocyte apoptosis. MiR-377-3p played opposite roles in cell proliferation and apoptosis. Moreover, PRNCR1 suppressed the role of miR-377-3p. Conclusions Therefore, PRNCR1 is was detected in cytoplasm and regulates synoviocyte proliferation and apoptosis in OA by sponging miR-377-3p.